Bacterial phospholipases C with dual activity: phosphatidylcholinesterase and sphingomyelinase - Monturiol‐Gross, Laura; Villalta‐Romero, Fabian; Flores‐Díaz, Marietta; Alape‐Girón, Alberto (FEBS open bio, 2021)
Bacterial phospholipases and sphingomyelinases are lipolytic esterases that are structurally and evolutionarily heterogeneous. These enzymes play crucial roles as virulence factors in several human and animal infectious diseases. Some bacterial phospholipases C (PLCs) have both phosphatidylcholinesterase and sphingomyelinase C activities. Among them, Listeria monocytogenes PlcB, Clostridium perfringens PLC, and Pseudomonas aeruginosa PlcH are the most deeply understood. In silico predictions of substrates docking with these three bacterial enzymes provide evidence that they interact with different substrates at the same active site. This review discusses structural aspects, substrate specificity, and the mechanism of action of those bacterial enzymes on target cells and animal infection models to shed light on their roles in pathogenesis. The aim of this review is to discuss similarities and differences among the most explored bacterial enzymes that have both phospholipase C and sphingomyelinase C activities. The structural aspects of three of those enzymes, their substrate specificity, and in silico substrate docking analysis are discussed, as well as their mechanisms of toxicity in cultured cells and animal models.